Photochemical Fluorimetric Determination of Cephradine - Cai, Wei-Ping; Ouyang, Yao-Guo; Lin, Xue-Yuan; Xu, Jin-Gou (Analytical letters, 1998)
In a weak acidic medium (pH 4.0). a photochemical reaction of cephradine occurs under the irradiation of ultraviolet light, forming a fluorescent product (γ ex = 334 nm, γ em = 442 nm). Based on this fact, a new photochemical fluorimetric method was developed for the determination of cephradine. The linear relationship between the fluorescence intensity and the concentration of cephradine is over the range of 0.01 - 4.0 μg/ml. The detection limit is 0.66 ng/ml (n = 11) and the relative standard deviation is 0.72% (n = 8). This method is simple and sensitive, and has been successfully applied to the determination of cephradine in urine samples. Mechanism of the photochemical reaction was also discussed.